Short term adherence tool predicts failure on second line protease inhibitor-based antiretroviral therapy - Court, Richard Gray (Department of Medicine, 2015)
The management of patients failing second line antiretroviral therapy (ART) is a critical area of study considering the increasing numbers of patients on second line regimens, and the expense and poor availability of third line ART. Most patients who experience virologic failure (VF) on second line ART in low-middle income countries fail due to poor adherence rather than antiretroviral resistance. Pharmacy refill is an easily implementable adherence measure which has shown to correlate with viral load monitoring and survival, and has potential over the short term to be used as a simple adherence tool to detect probable VF on second line ART. The benefit would be conservation of resources by rationally limiting need for viral load (VL) testing and, in those countries with access to third line ART, the need for resistance testing. We conducted an observational cohort study of patients who initiated second line ART at the McCord hospital ART clinic, â€œSinikithembaâ€ in Kwazulu-Natal, South Africa. Using clinical and pharmacy refill data extracted from the clinicâ€™s electronic database, we determined risk factors for VF. Three different methods of calculating short term pharmacy refill adherence were evaluated and compared with long term adherence after second line initiation. Different interval durations of short term pharmacy refill were also assessed to determine the optimum time period of pharmacy refill that correlates best with a virologic response on second line ART.